2008
DOI: 10.1002/mrm.21689
|View full text |Cite
|
Sign up to set email alerts
|

Altered white matter diffusion anisotropy in normal and preterm infants at term‐equivalent age

Abstract: To investigate white matter (WM) development, voxelwise analyses of diffusion tensor MRI (DTMRI) data, acquired from 12 very preterm and 11 preterm infants with gestational ages (GA) ranging from 25 to 29 and 29 to 32 weeks, respectively, and 10 newborn normal term infants were performed. T 2 relaxation measures were also generated to assess brain water content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
80
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 28 publications
14
80
0
Order By: Relevance
“…This finding is consistent with recent diffusion tensor imaging studies reporting increased fractional anisotropy in various cerebral white matter regions, including sensory tracts of premature neonates imaged at term equivalent compared with term neonates. 18,30 This finding was ascribed to an accelerated white matter development due to environmental stimulation. 18,30 Our metabolic findings reveal significant differences at short TE between in utero fetuses and premature neonates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is consistent with recent diffusion tensor imaging studies reporting increased fractional anisotropy in various cerebral white matter regions, including sensory tracts of premature neonates imaged at term equivalent compared with term neonates. 18,30 This finding was ascribed to an accelerated white matter development due to environmental stimulation. 18,30 Our metabolic findings reveal significant differences at short TE between in utero fetuses and premature neonates.…”
Section: Discussionmentioning
confidence: 98%
“…18,30 This finding was ascribed to an accelerated white matter development due to environmental stimulation. 18,30 Our metabolic findings reveal significant differences at short TE between in utero fetuses and premature neonates. Almost all metabolic ratios expressed with water tissue signal intensity as a reference were higher in the group of premature neonates.…”
Section: Discussionmentioning
confidence: 98%
“…Diffusion measures in preterm infants, in particular ADC, have been shown to be altered at term-equivalent age and to be predictive of later neurodevelopmental outcomes (25). Preterm infants at term equivalent often display alterations in diffusion measures, with elevation in ADC and reduction in anisotropy relative to term control infants (26). Although no data on the neuropathological correlates for these alterations in white matter diffusion measures exist, it is plausible that they result from either delay in development and/or injury with loss of oligodendroglia and/or axonal components of the cerebral white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown altered white matter diffusion anisotropy in preterm compared with normal-term infants, but it should be emphasized that results differ from 1 study to another. 7,19,49,50 Moreover, if subtle white matter lesions had occurred in some of the children born prematurely, it is unlikely that they would be distributed homogeneously and symmetrically in all of the regions so that linear FA increases with age would not be found.…”
Section: Discussionmentioning
confidence: 99%